Are the energy literacy, financial knowledge, and education level faces of the same coin?. (June 2022) - Martins, Ana; Madaleno, Mara; Ferreira Dias, Marta
Abstract: Education, financial knowledge, and energy literacy are seen as powerful tools that empower citizens and help them make informed decisions. Considering that both education and financial knowledge are often associated with better levels of energy literacy, we consider it important to check if there are common determinants between these three variables. Using a questionnaire applied to Portuguese university members (students, teachers, and technicians), we also tried to infer whether the factors that influence these variables are common among men and women. The results show that energy knowledge has an influence, not only on the level of energy literacy but also on the level of education and the level of financial knowledge.